Plant systematics : a phylogenetic approach / (Acc: P7450) - Judd, W. S. Campbell, C. S., Kellogg, E. A., Stevens, P. F., & Donoghue, M. J. (USA: Sinaur Associates, Inc., 2018)
A comprehensive introduction to vascular plant phylogeny, the fourth edition of Plant Systematics reflects changes in the circumscription of several families in order to represent monophyletic groups, following the classification of the Angiosperm Phylogeny Group (and recent phylogenetic analyses). Appendices cover botanical nomenclature as well as field and herbarium methodology. The text is copiously illustrated, using in large part the informative analytical drawings developed as part of the Generic Flora of the Southeastern United States project. Plant Systematics: A Phylogenetic Approach, Fourth Edition, is appropriate for any course devoted to the systematics of angiosperms or vascular plants and, secondarily, for local flora courses. The text assumes no prerequisites other than introductory botany or biology.
Includes bibliographical references and indexes.
Keywords: 1. Plant 2. Phylogenetics